LEGAL IMPLEMENTATION FOR ZAKAT MANAGEMENT PERFORMERS IN INDONESIA - Sulaiman; Ismaidar (Universitas Efarina, 2023)
Zakat is one of the obligations of Muslims which has been stipulated in the Al-Quran and explained in detail in the al-hadith of the Prophet Muhammad regarding its application, and also in the ijma' of the ulama. Management of the National Amil Zakat institution which manages, collects and utilizes zakat, infaq and alms throughout Indonesia, which consists of government and community elements. This research is qualitative research with Normative research methods. This research was carried out by looking for data sourced from laws, previous research, and from several references, especially in the section on how legal sanctions for managing zakat without permission are reviewed from Law no. 23 of 20211 and looking at the implementation of Law No. 23 of 2011, especially in article 22 concerning Zakat issued by muzakki will be deducted from taxable income. The results of this research are that managing zakat without permission will receive legal sanctions in the form of imprisonment for a minimum of 1 year and a maximum of 5 years or a fine of Rp. 500,000,000,- and the implementation of Law Number 23 of 2011 concerning zakat management related to zakat payments made. by muzakki where the implementation of zakat paid is deducted from taxable income has not yet been implemented optimally in Suluruh Indonesia. This is because employees do not implement these rules and what is known is only the obligation to pay zakat.